A mix design methodology of slag and fly ash-based alkali-activated paste. (February 2022) - Sun, Beibei; Sun, Yubo; Ye, Guang; De Schutter, Geert
Abstract: In this paper, a series of experiments were conducted to systematically and quantitively explore the effects of control factors on the early age properties, i.e., workability and strength of slag and fly ash-based alkali-activated paste (BFS/FA-AAP). The control factors on the workability (flowability and setting time) of BFS/FA-AAP include the Na2 O/b ratio, the SiO2 /Na2 O ratio, the w/b ratio, and the BFS/b ratio. The control factors on strength (compressive strength and flexural strength) of BFS/FA-AAP further also include the curing condition and the curing age. The results show that a higher BFS/b ratio and Na2 O/b ratio could increase the strength while decreasing the workability. A higher w/b ratio could increase the workability while slightly decreasing the strength. Higher SiO2 /Na2 O ratio increases both strength and workability. Despite that, higher Na2 O/b ratio and SiO2 /Na2 O ratio could hinder the strength development. Sealed curing condition is proved to be a simple but efficient way to assure the steady strength development of BFS/FA-AAP. Although the strength of BFS/FA-AAP could generally stabilize after 90 days, the strength development rate varies with different mix proportions. In addition, a general methodology have been proposed to predict the compressive strength of BFS/FA-AAP and verified with experiments. Finally, a mix design table is proposed for the preliminary design of BFS/FA-AAP according to the principle of satisfying early age requirements.